Analysis of the Salmonella typhimurium proteome through environmental response toward infectious conditions - Adkins, Joshua N; Mottaz, Heather M; Norbeck, Angela D; Gustin, Jean K; Rue, Joanne; Clauss, Therese R W; Purvine, Samuel O; Rodland, Karin D; Heffron, Fred; Smith, Richard D (Molecular & cellular proteomics, 2006)
Salmonella enterica serovar Typhimurium (also known as Salmonella typhimurium) is a facultative intracellular pathogen that causes approximately 8,000 reported cases of acute gastroenteritis and diarrhea each year in the United States. Although many successful physiological, biochemical, and genetic approaches have been taken to determine the key virulence determinants encoded by this organism, the sheer number of uncharacterized reading frames observed within the S. enterica genome suggests that many more virulence factors remain to be discovered. We used a liquid chromatography-mass spectrometry-based "bottom-up" proteomic approach to generate a more complete picture of the gene products that S. typhimurium synthesizes under typical laboratory conditions as well as in culture media that are known to induce expression of virulence genes. When grown to logarithmic phase in rich medium, S. typhimurium is known to express many genes that are required for invasion of epithelial cells. Conversely stationary phase cultures of S. typhimurium express genes that are needed for both systemic infection and growth within infected macrophages. Lastly bacteria grown in an acidic, magnesium-depleted minimal medium (MgM) designed to mimic the phagocytic vacuole have been shown to up-regulate virulence gene expression. Initial comparisons of protein abundances from bacteria grown under each of these conditions indicated that the majority of proteins do not change significantly. However, we observed subsets of proteins whose expression was largely restricted to one of the three culture conditions. For example, cells grown in MgM had a higher abundance of Mg(2+) transport proteins than found in other growth conditions. A second more virulent S. typhimurium strain (14028) was also cultured under these same growth conditions, and the results were directly compared with those obtained for strain LT2. This comparison offered a unique opportunity to contrast protein populations in these closely related bacteria. Among a number of proteins displaying a higher abundance in strain 14028 were the products of the pdu operon, which encodes enzymes required for propanediol utilization. These pdu operon proteins were validated in culture and during macrophage infection. Our work provides further support for earlier observations that suggest pdu gene expression contributes to S. typhimurium pathogenesis.